Online lectures: An implementation of full e-learning action research - Roby Zulkarnain Noer; Sucahyo Mas’an Al Wahid; Rani Febriyanti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
This study aimed to determine whether there is an increase in student learning outcomes after the implementation of online learning using the WhatsApp platform in the Children with Special Needs (CSN) course. This research method was a classroom action research conducted online using the WhatsApp platform. The classroom action research was carried out in 2 cycles with the stages including planning, implementing, observing, and reflecting. The subjects of this study were 21 PGSD UBT students in semester 6 of the 2019/2020 academic year. The data collection techniques used were observation, interviews, questionnaires, and test questions. While the research instruments used were observation sheets, interview sheets, online learning implementation questionnaires, and test questions. The data obtained were analyzed using qualitative and quantitative. The results of the study showed that the percentage of learning outcomes before and after being given learning treatment using the WhatsApp platform experienced a significant increase and had reached 85% completeness criteria. The online learning through the WhatsApp platform has some advantages, such as ease of use and development of courage in the discussion process. While the weakness is related to the unstable network and the lack of direct experience obtained through observations related to CSN material that requires direct practice in the field. This study was conducted as a contribution to the selection of learning media in a situation of Covid-19 pandemic, which requires learning to be conducted online or remotely.